ANALISIS MANAJEMEN RISIKO TI PADA KEAMANAN DATA E - LEARNING DAN ASET IT MENGGUNAKAN NIST SP 800 – 30 Revisi 1 - Riszullah Ramadhan Putra; Eman Setiawan; Awalludiyah Ambarwati (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2019)
Abstract Information security is very important for companies and universities. Many negative impacts have been caused by universities if information security is not properly maintained. This study analyzes how university administrators can identify operational risk factors involved with e-Learning operations. The four main types of operational risks involved are data security risk, password security, process risk, and the risk of attacks from hackers. eLINA (E-Learning Narotama University) has never conducted a risk management assessment on an online-based learning web. To protect the web, as well as maintain the continuity of business processes, this study will use the NIST SP 800-30 Revision 1 method, which consists of four processes, namely preparation for assessment, assessment, communicating results, and maintaining assessment. The final result of this assessment is a recommendation for a mitigation approach for the protection of the online learning system of Narotama University. Keywords: Risk Management, NIST SP 800-30 Revision 1, Information Security.